Statistical Analysis of Coal Beneficiation Performance in a Continuous Air Dense Medium Fluidized Bed Separator. Issue 1 (2nd January 2017) - Azimi, Ebrahim; Karimipour, Shayan; Xu, Zhenghe; Szymanski, Jozef; Gupta, Rajender
ABSTRACT: In this study, the performance of a continuous air dense medium fluidized bed (ADMFB) separator is investigated for coal beneficiation. The full factorial experimental design method is used to study the effect of superficial air velocity ( U ), bed length ( T ), and bed height ( H ) on the clean-coal ash content, organic material recovery, and overall system separation efficiency. Optimum operating conditions are determined and followed by the effect of feed particle size on separation quality. Statistical analysis of the results revealed that H had no significant effect on product ash content while U and T had negative effects. A reduction in ash content from 19% to 10% was obtained once full bed length was utilized. The increase of all parameters had a negative effect on organic material recovery, while recovery was always above 88%. The only significant mutual interaction was found to be between T and H with even more effectiveness than U on the recovery. Separation efficiency increased by increasing the bed length and reached 20% once full bed length was utilized. The optimum operating condition was determined to be at U = 19.5 cm/s, T = full bed length, and H = 15 cm. It was observed that feeding finer particles deteriorated the beneficiation process.